2008
DOI: 10.1189/jlb.0907658
|View full text |Cite
|
Sign up to set email alerts
|

The role of chloride anion and CFTR in killing ofPseudomonas aeruginosaby normal and CF neutrophils

Abstract: Chloride anion is essential for myeloperoxidase to produce hypochlorous acid (HOCl) in neutrophils (PMNs). To define whether chloride availability to PMNs affects their HOCl production and microbicidal capacity, we examined how extracellular chloride concentration affects killing of Pseudomonas aeruginosa (PsA) by normal neutrophils. PMN-mediated bacterial killing was strongly dependent on extracellular chloride concentration. Neutrophils in a chloride-deficient medium killed PsA poorly. However, as the chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
134
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 40 publications
8
134
1
Order By: Relevance
“…This is in agreement with a recent detailed analysis using fluorescence ratio imaging to measure the endosomal pH against an internal standard, which convincingly demonstrated that phagolysosomal acidification in macrophages is CFTR-independent (Haggie & Verkman, 2007). It has been reported that in human neutrophils CFTR channel dysfunction affects neutrophil chlorination of phagocytized bacteria (Painter et al, 2006(Painter et al, , 2008, raising the possibility that CFTR contributes to bacterial clearance rather than phagosomal acidification. Our experiments with B. cenocepacia-infected CFTR-defective macrophages showing an extended delay in the trafficking of BcCVs to lysosomes do indeed support a role for CFTR in the mechanism of clearance of the intracellular infection, as we have shown before that B. cenocepacia localized to the lysosome rapidly loses cell envelope integrity (Lamothe et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
“…This is in agreement with a recent detailed analysis using fluorescence ratio imaging to measure the endosomal pH against an internal standard, which convincingly demonstrated that phagolysosomal acidification in macrophages is CFTR-independent (Haggie & Verkman, 2007). It has been reported that in human neutrophils CFTR channel dysfunction affects neutrophil chlorination of phagocytized bacteria (Painter et al, 2006(Painter et al, , 2008, raising the possibility that CFTR contributes to bacterial clearance rather than phagosomal acidification. Our experiments with B. cenocepacia-infected CFTR-defective macrophages showing an extended delay in the trafficking of BcCVs to lysosomes do indeed support a role for CFTR in the mechanism of clearance of the intracellular infection, as we have shown before that B. cenocepacia localized to the lysosome rapidly loses cell envelope integrity (Lamothe et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
“…Reduced expression of the patternrecognition receptor Toll-like receptor (TLR)2 has been reported on peripheral blood neutrophils from CF patients, and this was correlated with increased systemic tumour necrosis factor-a, but more dramatic effects on TLR expression are seen on transmigrated CF neutrophils [34], suggesting an important acquired effect secondary to factors within the lung microenvironment. Different groups have reported either normal [35] or somewhat reduced [36] ability of isolated peripheral blood CF neutrophils to kill Pseudomonas aeruginosa in vitro; importantly, HARTL et al [35] also found that CF neutrophils obtained from sputum or bronchoalveolar lavage had a dramatically attenuated bactericidal capacity with respect to comparable cells from healthy subjects or to the peripheral blood CF cells, strongly implicating an acquired rather than an intrinsic defect.…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunction or lack of CFTR expression in macrophages, neutrophils, and dendritic cells (DCs) results in an inflammatory phenotype (4,5,(8)(9)(10)(11). In addition, antigen presentation is affected in CF.…”
mentioning
confidence: 99%
“…The dysregulated cytokine secretion of CF epithelial cells plays an important role in creating the inflammatory milieu (3). It has become increasingly clear that the cystic fibrosis transmembrane regulator (CFTR) also plays a role in lung immune cells, and that the dysfunction of the CFTR affects immune cell responses (4)(5)(6)(7)(8)(9)(10)(11). The dysfunction of pulmonary immune cells in CF could result from the lack of their own CFTR function, or may be induced by the altered milieu created by defective CFTR function in epithelial cells (5,8).…”
mentioning
confidence: 99%